Pertanggungjawaban Pidana bagi Pelaku Penipuan Berkedok Robot Trading di Indonesia Perspektif Hukum Pidana Islam - Siti Nur Khadijah; Syamsuri (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2024)
Abstract : Technological developments have made investment activities easier. However, this is often abused to commit criminal acts in the form of illegal investments, also known as fraudulent investments, using trading robots. This is inseparable from the lure in the form of high profits offered by irresponsible parties. This study aims to analyze the legal consequences for the perpetrators of trading robot fraud and the compensation for victims as a form of legal protection for victims. This research is a normative legal research, whose legal material comes from laws and regulations. The result of this study is that no regulation specifically regulates the appropriate sanctions to be applied to fraudsters under the guise of trading robots. This is because Article 378 of the Criminal Code, Article 28 paragraph 1 of the ITE Law, and Article 45 letter a paragraph (1) of the ITE Law do not accommodate the elements of fraudulent acts under the guise of trading robots. Compensation to the victim can be done through a restitution mechanism pursued through a civil lawsuit. Meanwhile, in the criminal realm, the perpetrator can be subject to the Money Laundering Crime Article (TPPU) so that the victim's assets can be returned through the mechanism of confiscating the perpetrator's assets obtained from the proceeds of the crime. In Islamic criminal law, sanctions that can be applied to fraudsters under the guise of trading robots are ta'zir.